2021
DOI: 10.21037/atm-20-4684
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on the clinicopathological traits and outcomes of hospitalized liver hemangioma patients: a multicenter study

Abstract: Background: There is currently a lack of consensus regarding the clinical features, diagnosis, treatment indications and options, and risk assessment of hepatic hemangioma patients.Methods: This was a multicenter, real-world study that analyzed a large number of hepatic hemangioma cases in China and included patient data on epidemiology, diagnosis, treatment methods, and outcomes.Results: A total of 5,143 patients hospitalized for hepatic hemangioma were included, of whom 34.42% were male and 65.58% were femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Like our case who had abdominal pain duo to torsion of hemangioma around its stalk. Male to female ratio for liver hemangioma in-hospital patients is 1:1.9 and cavernous hemangioma is the most common pathological type of liver hemangioma [9]. In this case also the patient was a woman with cavernous giant liver hemangioma without malignancy in pathological report.…”
Section: Discussionmentioning
confidence: 63%
“…Like our case who had abdominal pain duo to torsion of hemangioma around its stalk. Male to female ratio for liver hemangioma in-hospital patients is 1:1.9 and cavernous hemangioma is the most common pathological type of liver hemangioma [9]. In this case also the patient was a woman with cavernous giant liver hemangioma without malignancy in pathological report.…”
Section: Discussionmentioning
confidence: 63%
“…These results suggest that when the diameter of a haemangioma increases, operative treatment becomes more complex, and there is a greater risk. Some scholars have also reported that operation time and blood loss significantly increase with haemangioma diameter [ 2 , 7 ]. This finding was also supported by Singh [ 24 ], who found that a larger haemangioma diameter increased the difficulty of the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that hepatectomy and haemangioma enucleation are safe and feasible if the indications are properly controlled [ 2 , 5 , 7 , 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…They typically need periodic observation during long-term follow-up. Although the reported incidence of spontaneous rupture of hepatic hemangioma is low (1–4%) ( 2 ), the mortality is as high as 36–39% ( 3 ). Compared to spontaneous rupture hemorrhage, intratumoral hemorrhage of hepatic hemangiomas is even rarer.…”
Section: Introductionmentioning
confidence: 99%